Psychological consequences of bullying in the secondary schools of Capricorn District, Limpopo Province - Setlhwana, Sekedi Onicca (University of Limpopo, 2016)
The study investigated prevalence rates and psychological consequences of bullying in schools within the Sekgosese West Circuit, Capricorn District, Limpopo Province. Participants were identified and drawn through stratified random sampling. The final sample consisted of 670 learners enrolled for Grades 8, 9 and 10, 49% of whom fell in the 14-15 years old age group, and 56% being female. Data were collected using a structured, composite questionnaire, within a cross-sectional research design. The results of the study show that most bullies and the bullied-bullies were male learners, and rates of the bullied were evenly split between male and female learners. The largest proportions of bullies and the bullied-bullies were the youngest and the oldest age groups. The oldest group was the largest group of the bullied. The largest proportions of the bullies and the bullied were in grade 8, and the proportion of the bullied-bullies was almost the same in grades 8 and 10, edging the proportion found in grade 9. The investigation also found that learners who were not involved in bullying experienced the least amounts of psychological distress. However, the bullies, bullied and bullied-bullies obtained mean scores that were not statistically different from each other from the measures of psychological distress used in this study. It is concluded from the results of the study that bullying is common in the Sekgosese West Circuit, and its psychological consequences are same for all the learners who involved in bullying one way or another. It is recommended that the study be replicated in other districts of Limpopo, and the context of bullying itself be considered as a candidate for inclusion in future studies. Key words: Bullied, bully, bullied-bully, learners, psychological distress
Thesis (M. A. (Research Psychology)) --University of Limpopo, 2016
Keywords: Bullies; Bullying; Psychological distress; Bullying; Bullying in schools - Prevention